การต่อรองของครูเพื่อให้มีชีวิตรอดท่ามกลางสถานการณ์ความรุนแรงในพื้นที่จังหวัดปัตตานี - บุญปราการ, เก็ตถวา; และหีม, เกษตรชัย (วารสารวิทยบริการ มหาวิทยาลัยสงขลานครินทร์ | Academic Services Journal, Prince of Songkla University; Vol 30 No 3 (2562): Academic Services Journal, Prince of Songkla UniversityDO - 10.14456/asj-psu.2019.43, 2019)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อศึกษาการต่อรองของครูเพื่อให้มีชีวิตรอดท่ามกลางสถานการณ์ความรุนแรงในพื้นที่จังหวัดปัตตานี โดยใช้วิธีวิจัยเชิงคุณภาพ เก็บข้อมูลจากการสังเกตแบบไม่มีส่วนร่วมจากกิจกรรมของครูที่อยู่ในโรงเรียน และการใช้ชีวิตประจำวันในพื้นที่อื่น สัมภาษณ์แบบเจาะลึกจากผู้ให้ข้อมูล จำนวน 18 คน ได้แก่ ครู ครอบครัว เพื่อน เจ้าหน้าที่ภาครัฐ ทหาร นักเรียน ในพื้นที่จังหวัดปัตตานี วิเคราะห์ข้อมูลโดยการนำข้อมูลมาจำแนกหมวดหมู่ ตีความ และสร้างข้อสรุป นำเสนอด้วยวิธีพรรณนาเชิงวิเคราะห์ ผลการวิจัยพบว่า ครูมีการต่อรองระดับกลุ่มและระดับปัจเจกชน ในระดับกลุ่มมีการสร้างเครือข่ายความร่วมมือผ่านเจ้าหน้าที่รัฐ ทหาร ตำรวจ สมาพันธ์ครูปัตตานี และสภาประชาสังคมชายแดนใต้ การหามาตรการสร้างความปลอดภัยภายใต้นโยบายทหาร พบว่า มีการช่วยเหลือครูในการเดินทางไปกลับระหว่างบ้านกับโรงเรียนหลากหลายวิธี ส่วนการต่อรองระดับปัจเจกบุคคล พบว่า ครูได้ช่วยเหลือตัวเองโดยการแสวงหาวิธีการหรืออาวุธไว้ป้องกันตนเองและไม่ไปในพื้นที่เสี่ยง คำสำคัญ: การต่อรองของครู, การมีชีวิตรอด, สถานการณ์ความรุนแรง   This research aimed to study the negotiation of teacher to survive the violence in Pattani Province. The study was according to qualitative data were collected from non-participant observation of teacher activity in school and daily living in other areas. In-depth interviews from 18 informants, including teachers, families, friends, government officials, soldiers, students in Pattani. The data were analyzed by classification, interpretation, and conclusions of the study and was presented by descriptive analysis. The research found that teachers had group and individual bargaining at the group level. There was a network of cooperation through the military state police, the Pattani Teacher Confederation, and the Southern Border Civil Society. Finding security measures under the military policy has found that teachers have a great deal of help in getting back and forth between home and school. Individual negotiation shows that teachers help themselves by seeking ways or weapons to protect themselves and not in risky areas. Keywords: teacher negotiation, survival, violence situation